2021
DOI: 10.7554/elife.64348
|View full text |Cite
|
Sign up to set email alerts
|

Robust, coherent, and synchronized circadian clock-controlled oscillations along Anabaena filaments

Abstract: Circadian clocks display remarkable reliability despite significant stochasticity in biomolecular reactions. We study the dynamics of a circadian clock-controlled gene at the individual cell level in Anabaena sp. PCC 7120, a multicellular filamentous cyanobacterium. We found significant synchronization and spatial coherence along filaments, clock coupling due to cell-cell communication, and gating of the cell cycle. Furthermore, we observed low-amplitude circadian oscillatory transcription of kai genes compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 72 publications
4
30
2
Order By: Relevance
“…This was strongly supported by genetic perturbation of the septal junctions connecting adjacent Anabaena sp. PCC 7210 cells, which resulted in much faster decay in spatial autocorrelation and significantly reduced order parameter (Arbel-Goren et al, 2021). Thus, these latest results have demonstrated that circadian coupling in cyanobacteria can exist, at least via direct cytoplasmic connections in filamentous species.…”
Section: Ll Open Accessmentioning
confidence: 77%
See 3 more Smart Citations
“…This was strongly supported by genetic perturbation of the septal junctions connecting adjacent Anabaena sp. PCC 7210 cells, which resulted in much faster decay in spatial autocorrelation and significantly reduced order parameter (Arbel-Goren et al, 2021). Thus, these latest results have demonstrated that circadian coupling in cyanobacteria can exist, at least via direct cytoplasmic connections in filamentous species.…”
Section: Ll Open Accessmentioning
confidence: 77%
“…popular, particularly for single-cell-level observation (Chabot et al, 2007;Martins et al, 2016;Chew et al, 2018;Arbel-Goren et al, 2021).…”
Section: Ll Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the cellular C/N balance is highly regulated in Anabaena ( 32 ), it is plausible that filaments of the WT that fixed little N were affected in CO 2 fixation, as observed for unicellular cyanobacteria after several hours of N deprivation ( 33 ). On the other hand, different filaments could exhibit dissimilar metabolic states because they can be at different positions in the circadian cycle, which runs in individual Anabaena filaments even under constant light ( 34 ). Thus, the possibility that stretches of vegetative cells with low photosynthetic activity provide a heterocyst with insufficient reduced C affecting N 2 fixation should also be considered.…”
Section: Discussionmentioning
confidence: 99%